Copper Sulfide Nanodisks and Nanoprisms for Photoacoustic Ovarian Tumor Imaging. (2nd June 2019) - Wang, Junxin; Hsu, Su‐wen; Gonzalez‐Pech, Natalia; Jhunjhunwala, Anamik; Chen, Fang; Hariri, Ali; Grassian, Vicki; Tao, Andrea; Jokerst, Jesse V.
Abstract: Transvaginal ultrasound is widely used for ovarian cancer screening but has a high false‐positive rate. Photoacoustic imaging provides additional optical contrast to supplement ultrasound and might be able to improve the accuracy of screening. Two copper sulfide (CuS) nanoparticle types (nanodisks and triangular nanoprisms) are reported as photoacoustic contrast agents for imaging ovarian cancer. Both CuS nanoprisms and nanodisks are ≈6 nm thick and ≈26 nm wide and are coated with poly(ethylene glycol) to make them colloidally stable in phosphate‐buffered saline for at least two weeks. The CuS nanodisks and nanoprisms reveal strong localized surface plasmon resonances with peak maxima at 1145 and 1098 nm, respectively. Both nanoparticle types have strong and stable photoacoustic intensity with detection limits below 120 pm . The circular CuS nanodisk remains in the circulation of nude mice ( n = 4) and xenograft 2008 ovarian tumors ( n = 4) 17.9‐fold and 1.8‐fold more than the triangular nanoprisms, respectively. Finally, the photoacoustic intensity of the tumors from the mice ( n = 3) treated with CuS nanodisks is threefold higher than the baseline. The tumors treated with nanodisks have a characteristic peak at 920 nm in their spectrum to potentially differentiate the tumor from adjacent tissues. Abstract : Copper sulfide nanodisks and nanoprisms are employed as photoacoustic contrast agents for ovarian tumor imaging. While these two nanoparticles have nearly identical length, thickness, and surface charge, nanodisks have 1.8‐fold higher accumulation than nanoprisms in xenograph human OV 2008 tumors. This difference indicates the importance of nanoparticle morphology in nanomedicine.